Lymphatic mapping and sentinel lymph node biopsy with real-time fluorescence (Revista Argentina de Cirugía, 2021)
Background: sentinel lymph node (SLN) biopsy is a standard staging procedure in different neoplasias.Objetive: to describe the technique and early results of lymphatic mapping and SLN biopsy with realtime infrared fluorescence with indocyanine green (IG), in patients with melanoma, breast cancer and oral cavity carcinoma.Materials and methods: radioactive tracer was injected few hours prior to surgery and lymphoscintigram was performed;IG was injected after induction of anaesthesia. The lymphatic drainage and the SLN were detected by real-time fluorescence imaging, and the SLN withgammaprobe.Results: SLN was identified by both methods in the 16 patients; three additional SLN were found with IG. It was not reported any acute side effect related to the procedure.Conclusions: the use of IG as a fluorescence dye proved to be a useful and safe option for SLN biopsy, and it seems to be a promising technique for the near future.
Keywords: sentinel lymph node; indocyanine green; fluorescence; melanoma; breast cancer; oral cavity cancer